The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.2807/1560-7917.es.2016.21.10.30156
|View full text |Cite
|
Sign up to set email alerts
|

Waning immunity against mumps in vaccinated young adults, France 2013

Abstract: In 2013, 15 clusters of mumps were notified in France; 72% (82/114) of the cases had been vaccinated twice with measles-mumps-rubella vaccine. To determine whether the risk of mumps increased with time since the last vaccination, we conducted a case-control study among clusters in universities and military barracks. A confirmed case had an inflammation of a salivary gland plus laboratory confirmation in 2013. A probable case presented with inflammation of a salivary gland in 2013 either lasting for > 2 days or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
76
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 26 publications
(67 reference statements)
2
76
2
2
Order By: Relevance
“…Mumps immunity has also been shown to wane with time after vaccination [31,32]. However, our study found absence of mumps antibodies in all four age groups.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Mumps immunity has also been shown to wane with time after vaccination [31,32]. However, our study found absence of mumps antibodies in all four age groups.…”
Section: Discussioncontrasting
confidence: 63%
“…However, our study found absence of mumps antibodies in all four age groups. In order to better prepare for future outbreaks, booster doses of MMR may be needed in vaccination programs, especially for the younger age groups whose immunity is induced by vaccination [31].…”
Section: Discussionmentioning
confidence: 99%
“…Most cases occurred on college and university campuses among young adults, nearly all of whom had been vaccinated during early childhood (9). Data from outbreak studies showed that the odds of developing mumps increased by 10 to 27% with each year postvaccination, suggesting waning immunity as the basis for these outbreaks (10,75). This observation was consistent with data from other studies that showed that mumps virus-neutralizing Ab titers declined significantly with time postvaccination (76,77), although the level of Ab that confers protection was not known.…”
Section: Mumps Vaccinesmentioning
confidence: 99%
“…However, mumps outbreaks have occurred in the United States in the last decade, including the large outbreak centered around a university in Iowa, which had over 5,000 cases in 2006 [3639]. Mumps outbreaks have also been reported in vaccinated populations in Europe and Asia [2023,40,41]. None of these outbreaks were associated with a genotype A MuV, which was the Jeryl Lynn vaccine genotype.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that this decrease may contribute to some of the recent outbreaks. It has been shown that there is variation in serum neutralizing antibodies among people over time [21,4143]. Poor immune responses or waning immunity may result in some individuals dropping below a protective threshold.…”
Section: Discussionmentioning
confidence: 99%